Quadruple Fixed Point Theorems under Nonlinear Contractive Conditions in Partially Ordered Metric Spaces - Erdal Karapınar; Wasfi Shatanawi; Zead Mustafa (Journal of Applied Mathematics)
We prove a number of quadruple fixed point theorems under 𝜙-contractive conditions for a mapping 𝐹∶𝑋4→𝑋 in ordered metric spaces. Also, we introduce an example to illustrate the effectiveness of our results.